1998
DOI: 10.1093/oxfordjournals.pcp.a029423
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Pattern of the Gene for NPK1 Protein Kinase Related to Mitogen-Activated Protein Kinase Kinase Kinase (MAPKKK) in a Tobacco Plant: Correlation with Cell Proliferation

Abstract: Mitogen-activated protein kinase (MAPK) cascades consist of members of three families of protein kinases: the MAPK family, the MAPK kinase family, and the MAPK kinase kinase (MAPKKK) family. Some of these cascades have been shown to play central roles in the transmission of signals that control various cellular processes including cell proliferation. Protein kinase NPK1 is a structural and functional tobacco homologue of MAPKKK, but its physiological function is yet unknown. In the present study, we have inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 27 publications
1
38
0
1
Order By: Relevance
“…Tobacco plants, Nicotiana tabacum SR1, were grown on Murashige and Skoog medium plates at 26°C under cycles of 16 h of light and 8 h of dark (Nakashima et al 1998). Transgenic BY-2 cells and tobacco plants were generated by Agrobacterium-mediated transformation (Onouchi et al 1995;Nakashima et al 1998), in which LBA4404 strain was used.…”
Section: Plant Materials and Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco plants, Nicotiana tabacum SR1, were grown on Murashige and Skoog medium plates at 26°C under cycles of 16 h of light and 8 h of dark (Nakashima et al 1998). Transgenic BY-2 cells and tobacco plants were generated by Agrobacterium-mediated transformation (Onouchi et al 1995;Nakashima et al 1998), in which LBA4404 strain was used.…”
Section: Plant Materials and Transformationmentioning
confidence: 99%
“…NPK1 and its Arabidopsis orthologous genes, ANP1/2/3, are transcribed in proliferating and division-competent cells or in organs rich in these cells, an observation that suggests their role in cell division (Banno et al 1993;Nishihama et al 1997;Nakashima et al 1998). Recently, it was reported that overexpression of the kinase domain of NPK1 or ANP1 in maize or Arabidopsis cells results in suppression of auxin-induced gene expression and in activation of stress signaling (Kovtun et al 1998(Kovtun et al , 2000.…”
mentioning
confidence: 99%
“…The Arabidopsis ANP genes were isolated originally as a result of their homology with the tobacco NPK1 gene (Banno et al, 1993;Nishihama et al, 1997;Machida et al, 1998;Nakashima et al, 1998). Work by Nishihama et al (2001) has demonstrated that the NPK1 gene is involved in the regulation of cytokinesis in tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…NPK1 regulates cytokinesis (Nakashima et al, 1998) as well as the effector-triggered immunity and development in Nicotiana benthamiana (Jin et al, 2002). ANPs have also been reported to be involved in the inhibition of auxin-induced gene expression.…”
mentioning
confidence: 99%